Expert consensus statement on acute hepatic porphyria in Belgium. Issue 4 (4th July 2022) - Gilles, Axelle; Vermeersch, Sebastian; Vermeersch, Pieter; Wolff, Fleur; Cotton, Frederic; Tilleux, Sebastien; Cassiman, David
ABSTRACT: Acute hepatic porphyrias (AHP) are a group of four different rare to ultra-rare, severely debilitating, and sometimes fatal diseases that significantly impact patients' lives: 5‐aminolevulinic acid (ALA) dehydratase deficiency porphyria (ADP), acute intermittent porphyria (AIP), hereditary coproporphyria (HCP), and variegate porphyria (VP). Based on literature estimates, a conservative estimate of the number of AHP patients in Belgium requiring treatment, defined as patients experiencing recurrent attacks and/or chronic debilitating symptoms, is likely limited to 11–34 patients. These patients face a considerable unmet need, as there is currently no pharmaceutical treatment available that effectively prevents attacks and has an impact on other chronic symptoms of the disease. A panel consisting of the two European Porphyria Network 1 (EPNet) centers in Belgium (Center for inborn errors of metabolism of UZ Leuven and the 'Centre Belge des Porphyries' of Erasme Hospital and LHUB-ULB) participated in an advisory board on 24 January 2020. Representatives of the sponsoring pharmaceutical company, Alnylam Pharmaceuticals, organized and attended the meeting. The objective of the meeting was to obtain expert input on the state-of-the-art clinical practice of AHP in Belgium. Following this meeting, this expert consensus statement was drafted, in collaboration with and coordinated by the EPNet centers in Belgium. This statement provides an overview of the state-of-the art in AHP, by means of a concise overview of AHP pathophysiology, clinical manifestations, and burden of disease, (Belgian) epidemiology, treatments, and proposed organization of care.